Skull Morphology of California and Steller Sea Lions in the Pacific Northwest: Evidence for Potential Hybridization - Ada Iris García García; Deborah A. Duffield (Marine Mammal Science, 2026)
Eumetopias jubatus (Steller sea lions) that breed on the Oregon coast are generally smaller than those found in Alaska. During the breeding season, male Zalophus californianus (California sea lions) move past E. jubatus rookeries in Oregon on their way to breeding rookeries in Southern California. Introgression by male Z. californianus could potentially explain the difference in size of Oregon E. jubatus relative to other E. jubatus populations. To assess whether morphologically detectable hybrids occur between Z. californianus and E. jubatus in Oregon, we used traditional skull morphometrics and Principal Component Analysis to identify individuals with intermediate morphological characteristics. Multiple range comparisons were used to determine which groups differed significantly. The comparisons revealed significant cranial morphological variation within each species' clusters and identified two male Z. californianus that overlapped with the male E. jubatus cluster, as well as two female E. jubatus that overlapped with the male Z. californianus cluster, suggesting potential hybrid status. These results support the possibility that long‐term introgression between these two species may account for the observed size difference of the Oregon and Alaskan E. jubatus .

Life history, reproductive, and demographic parameters for bottlenose dolphins (Tursiops truncatus) in Sarasota Bay, Florida - Randall S. Wells; Aleta A. Hohn; Michael D. Scott; Jay C. Sweeney; Forrest I. Townsend; Jason B. Allen; Aaron A. Barleycorn; Katherine A. McHugh; Kim Bassos-Hull; Gretchen N. Lovewell; Deborah A. Duffield; Cynthia R. Smith; et al. (Frontiers in Marine Science, 2025)
Studies of the resident community of bottlenose dolphins ( Tursiops truncatus ) of Sarasota Bay, Florida, have been conducted for more than 50 years. Detailed histories have been collected for resident individuals through integrated observations, systematic photographic identification surveys, tagging and tracking, catch-and-release health assessments, remote biopsy sampling, and stranding response. This has produced a unique dataset documenting life history milestones and vital rates of a small cetacean. Analyses of data from 482 resident Sarasota Bay dolphins have revealed estimated maximum life spans of 67 years for females and 52 years for males. For females, predicted age at sexual maturation is 8.5 years, with a predicted age at first reproduction of 9.6 years. Females were observed to give birth when 6-48 years of age, and have been documented with as many as 12 calves, with 45% observed post-separation. Ten percent of females were considered to be reproductively senescent, having gone >13 years without producing a calf. For males, predicted age at sexual maturation is 10 years. Males 10-43 years old sired calves, producing up to 7 calves each. The average calving interval was 3.5 years, albeit with effects due to mother’s age, birth order, and calf survival. Seasonal reproduction was evident, with 81% of births occurring during May-July. Mean annual birth rate was 0.071. Mean annual fecundity was 0.182 births/adult female (defined as females 6 yrs or older). Recruitment rate through reproduction was estimated to be 0.050 based on calves surviving their first year. Immigration was infrequent, with an estimated annual rate of 0.003-0.013. Estimated mean annual maximum loss rate, from mortality, emigration, and changed identification characteristics, was 0.072. Periods of increased loss rates were related to environmental events, and factors that may be important to long-term population resilience were suggested.

Worldwide phylogeography of rough‐toothed dolphins ( Steno bredanensis ) provides evidence for subspecies delimitation - G. Renee Albertson; Alana Alexander; Frederick I. Archer; Susana Caballero; Karen K. Martien; Lenaïg G. Hemery; Robin W. Baird; Marc Oremus; M. Michael Poole; Deborah A. Duffield; Robert L. Brownell; Dan Kerem; et al. (Marine Mammal Science, 2022)
Rough‐toothed dolphins ( Steno bredanensis ) have a global tropical and subtropical distribution with oceanic, neritic, and island‐associated populations. To inform conservation and management for this species, we used sequences from the mtDNA control region ( n = 360), mitogenomes ( n = 19), and six nuclear introns ( n = 35) to provide multiple lines of evidence to critically evaluate the potential taxonomic status of rough‐toothed dolphins. Using samples from the Pacific, Indian, and Atlantic Oceans, we examined the null hypothesis that rough‐toothed dolphins are one panmictic species and the alternate hypothesis of oceanic subspecies. Phylogenetic analyses of mitogenomes revealed a private Atlantic clade sister to a larger cosmopolitan clade including individuals from all tropical and subtropical oceans. We dated the split between the Atlantic clade and the cosmopolitan clade to 890,000 years ago. We determined that Atlantic rough‐toothed dolphins could be correctly diagnosed with 98% accuracy with the mtDNA control region and calculated the net nucleotide divergence as 0.02. Population level analyses revealed significant genetic differentiation using mtDNA among most regions, while significant differentiation using nuclear markers occurred only between the Atlantic and the Indian/Pacific regions. Therefore, the oceanic divergence and diagnosability of rough‐toothed dolphins in the Atlantic and the Indian/Pacific Oceans meet proposed criteria for recognition as two subspecies.

Cetacean Strandings in the US Pacific Northwest 2000–2019 Reveal Potential Linkages to Oceanographic Variability - Amanda J. Warlick; Jessica L. Huggins; Dyanna M. Lambourn; Deborah A. Duffield; Dalin N. D’Alessandro; James M. Rice; John Calambokidis; M. Bradley Hanson; Joseph K. Gaydos; Steven J. Jeffries; Jennifer K. Olson; Jonathan J. Scordino; et al. (Frontiers in Marine Science, 2022)
Studying patterns in marine mammal stranding cases can provide insight into changes in population health, abundance, and distribution. Cetaceans along the United States West coast strand for a wide variety of reasons, including disease, injury, and poor nutritional status, all of which may be caused by both natural and anthropogenic factors. Examining the potential drivers of these stranding cases can reveal how populations respond to changes in their habitat, notably oceanographic variability and anthropogenic activities. In this study, we aim to synthesize recent patterns in 1,819 cetacean strandings across 26 species in the Pacific Northwest from 2000 to 2019 to compare with previous findings. Additionally, we aim to quantify the effects of localized and basin-scale oceanographic conditions on monthly stranding cases for five focal species using generalized additive models in order to explore potential relationships between strandings and changes in biophysical features that could affect foraging conditions or other important physiological cues. Our results suggest that strandings of harbor porpoises, gray whales, humpback whales, Dall’s porpoises, and striped dolphins are correlated with certain environmental variables, including sea surface temperature, chlorophyll concentration, and the Pacific Decadal Oscillation depending on the species. While it remains challenging to identify the causal mechanisms that underlie these relationships for a given species or population based on its utilization of such a complex ecosystem, improving our understanding of periods of increased strandings can enhance our knowledge of how these species interact with their environment and assist conservation and management efforts. This study enhances the utility of stranding records over time beyond simply reporting trends and has broader applicability to other geographic regions amid global climate change.

Organochlorine exposure and health effects in stranded Steller sea lions ( Eumetopias jubatus ) and Pacific harbor seals ( Phoca vitulina richardii ) from Oregon and southern Washington coasts - Deke Gundersen; Daniel Josefchak; Deborah A. Duffield; Dalin N. D'Alessandro; James M. Rice (Marine Mammal Science, 2021)
Organochlorine (OC) pesticides and polychlorinated biphenyls (PCBs) have been detected in a variety of marine mammal species at levels associated with adverse health effects. Little is known about OC levels and impacts on health in pinnipeds with different life histories. We determined the health and levels of 18 OC pesticides and 16 PCB congeners in blubber samples from 20 Steller sea lions and 39 Pacific harbor seals stranded from Oregon and Southern Washington. The most commonly detected OC at the highest concentration was p,p′‐ dichlorodiphenyldichloroethylene (DDE). PCBs were detected in all samples as well. Hypothesis testing indicated that diseased Steller sea lions (males and females combined) had higher contaminant concentrations than healthy Steller sea lions, and diseased Pacific harbor seals had higher concentrations of total OCs than healthy animals. Differences were also noted between diseased and healthy animals when looking at individual sexes of each species. Diseased Steller sea lions had higher mean contaminant levels than diseased harbor seals and healthy Steller sea lions had higher mean contaminant concentrations than healthy Pacific harbor seals. These results show that species differences exist in both contaminant loads and sensitivity to contaminants, which may be due to differences in life histories and physiology.

Bone mineral density of the common bottlenose dolphin radius: A primary skeletal site for clinical bone densitometry and preliminary descriptive data set using archival specimens - James W. B. Powell; Deborah A. Duffield; Jonathan J. Kaufman; Gangming Luo; Gretchen N. Lovewell; Wayne E. McFee (Marine Mammal Science, 2021)
We examined bone mineral density (BMD) in the pectoral flipper of the common bottlenose dolphin, Tursiops truncatus . These data addressed the need to define a comprehensive target site for osteodensitometric assessment and to provide a descriptive bone density data set for this species. We analyzed 388 radii from 279 bottlenose dolphins using dual energy X‐ray absorptiometry (DXA), the accepted standard in human medical studies. Radii were examined for differences based on sex, age, total body length, handedness, geographical affinity, and nutritional status at death. BMD increased with age and body length ( R 2 = 0.58, p t = −1.60, p > .05) or right and left flippers ( t = −1.76, p > .05). Additionally, no statistically significant differences were observed based on geographical region ( t = −0.190, p > .05) or nutritional status ( F = 0.83, p > .05). These results support the use of these findings as a preliminary descriptive data set for BMD in bottlenose dolphins and detail a primary skeletal site for clinical assessment of bone density for the species. As this study relies on archived museum specimens collected from dolphins at time of death, further studies regarding bone density may be better addressed using live dolphins with known health status.

Prey-Related Asphyxiation in Harbor Porpoises (Phocoena phocoena) along the U.S. West Coast: Importance of American Shad (Alosa sapidissima) on Adult Female Harbor Porpoise Mortality - Cindy R. Elliser; John Calambokidis; Dalin N. D’Alessandro; Deborah A. Duffield; Jessica L. Huggins; James Rice; Isidore Szczepaniak; Marc Webber (Oceans, 2020)
Harbor porpoise (Phocoena phocoena) diets are predominantly comprised of small fish species (<30 cm) and squid. However, predation on larger species (up to 63 cm) occurs, raising the question of increased risk of asphyxiation associated with this behavior. Literature was reviewed and stranding data from 1983 to 2020 from the U.S. West Coast (including California, Oregon and Washington) were searched for cases of prey-related asphyxiation of harbor porpoises and analyzed in relation to age, sex, reproductive status and prey species. Twenty-nine cases were documented. Twenty-seven cases involved large prey; non-native American shad caused the asphyxiation in 87% of the cases where the prey species was identified. The majority (92%) of harbor porpoises were females, and at least 83.3% were pregnant or recently post-partum. Reproductively active females may be more likely to attempt potentially risky behavior in order to compensate for their increased energetic needs. Increasing numbers of non-native American shad may pose a unique danger in this region for harbor porpoises not adapted to deal with the challenges of that prey. This may be a cause for concern, as there is likely an interaction between location, age and reproductive status on the diet composition and foraging strategies of harbor porpoises.

Bone density cannot accurately predict age in the common bottlenose dolphin, Tursiops truncatus - James W. B. Powell; Deborah A. Duffield; Jonathan J. Kaufman; Wayne E. McFee (Marine Mammal Science, 2019)

Organochlorine Contaminants in Blubber from Stranded Marine Mammals Collected from the Northern Oregon and Southern Washington Coasts: Implications for Re-introducing California Condors, Gymnogyps californianus, in Oregon - Deke T. Gundersen; Deborah A. Duffield; Tina Randall; Nate Wintle; Dalin N. D’Alessandro; James M. Rice; David Shepherdson (Bulletin of Environmental Contamination and Toxicology, 2013)

The application of GIS and spatiotemporal analyses to investigations of unusual marine mammal strandings and mortality events - Stephanie A. Norman; Jessie Huggins; Tim E. Carpenter; James T. Case; Dyanna M. Lambourn; Jim Rice; John Calambokidis; Joseph K. Gaydos; M. Bradley Hanson; Deborah A. Duffield; Sandra Dubpernell; Susan Berta; et al. (Marine Mammal Science, 2012)
In 2006–2007, an unusually high number of harbor porpoises ( Phocoena phocoena ) stranded along the Washington and Oregon coastlines. Spatiotemporal analyses were used to examine their ability to detect clusters of porpoise strandings during an unusual mortality event (UME) in the Pacific Northwest using stranding location data. Strandings were evaluated as two separate populations, outer coast and inland waters. The presence of global clustering was evaluated using the Knox spatiotemporal test, and the presence of local clusters was investigated using a spatiotemporal scan statistic (space–time permutation). There was evidence of global clustering, but no local clustering, supporting the hypothesis that strandings were due to more varied etiologies instead of localized causes. Further analyses at subregional levels, and concurrently assessing environmental factors, might reveal additional geographic distribution patterns. This article describes the spatial analytical tools applied in this study and how they can help elucidate the spatiotemporal epidemiology of other UMEs and assist in determining their causes. More than one spatial analytical technique should be used if the study objective is to detect and describe clustering in time and space and to generate hypotheses regarding causation of marine mammal disease and stranding events.

Total mercury in stranded marine mammals from the Oregon and southern Washington coasts - Nathan J. P. Wintle; Deborah A. Duffield; Nélio B. Barros (Deceased); Ronald D. Jones; James M. Rice (Marine Mammal Science, 2011)
Muscle samples from 105 marine mammals stranded along the Oregon and Washington coasts (2002–2009) were tested for levels of total mercury (THg) by Cold Vapor Atomic Fluorescence Spectrometry. The THg present is in the form of the highly toxic methylmercury. After normalizing tissue to 75% water weight, Steller sea lions and northern elephant seals exhibited the highest mean concentrations of THg followed by harbor seals, harbor porpoises, and California sea lions, 0.34 ± 0.278, 0.34 ± 0.485, 0.21 ± 0.216, 0.17 ± 0.169, and 0.15 ± 0.126 mg/kg normalized wet weight (ww), respectively. The mean normalized values demonstrate limited muscle methylmercury accumulation in these species in the Pacific Northwest. However, actual ww concentrations in some of the stranded carcasses may pose a risk to scavengers. Normalizing muscle mercury concentrations eliminated the variability from desiccation, and allowed for a clearer indication of the amount of mercury the animal accumulated before stranding.

Ancient DNA reveals genotypic relationships among Oregon populations of the sea otter (Enhydra lutris) - Kim Valentine; Deborah A. Duffield; Lorelei E. Patrick; David R. Hatch; Virginia L. Butler; Roberta L. Hall; Niles Lehman (Conservation Genetics, 2008)

IDENTIFYING PYGMY AND DWARF SPERM WHALES (GENUS KOGIA ) USING ELECTROSPRAY IONIZATION MASS SPECTROMETRY OF MYOGLOBIN AND HEMOGLOBIN - Deborah A. Duffield; Nélio B. Barros; Edgard O. Espinoza; Stephanie Ploen; Frances M. D. Gulland; John E. Heyning (Marine Mammal Science, 2003)